Repeated ischaemic preconditioning: a novel therapeutic intervention and potential underlying mechanisms. Issue 6 (1st June 2016) - Thijssen, Dick H. J.; Maxwell, Joseph; Green, Daniel J.; Cable, N. Timothy; Jones, Helen
New Findings: What is the topic of this review? This review discusses the effects of repeated exposure of tissue to ischaemic preconditioning on cardiovascular function, the attendant adaptations and their potential clinical relevance. What advances does it highlight? We discuss the effects of episodic exposure to ischaemic preconditioning to prevent and/or attenuate ischaemic injury and summarize evidence pertaining to improvements in cardiovascular function and structure. Discussion is provided regarding the potential mechanisms that contribute to both local and systemic adaptation. Findings suggest that clinical benefits result from both the prevention of ischaemic events and the attenuation of their consequences. Ischaemic preconditioning (IPC) refers to the phenomenon whereby short periods of cyclical tissue ischaemia confer subsequent protection against ischaemia‐induced injury. As a consequence, IPC can ameliorate the myocardial damage following infarction and can reduce infarct size. The ability of IPC to confer remote protection makes IPC a potentially feasible cardioprotective strategy. In this review, we discuss the concept that repeated exposure of tissue to IPC may increase the 'dose' of protection and subsequently lead to enhanced protection against ischaemia‐induced myocardial injury. This may be relevant for clinical populations, who demonstrate attenuated efficacy of IPC to prevent or attenuate ischaemic injury (and therefore myocardial infarct size). Furthermore, episodic IPC facilitates repeated exposure to local (e.g. shear stress) and systemic stimuli (e.g. hormones, cytokines, blood‐borne substances), which may induce improvement in vascular function and health. Such adaptation may contribute to prevention of cardio‐ and cerebrovascular events. The clinical benefits of repeated IPC may, therefore, result from both the prevention of ischaemic events and the attenuation of their consequences. We provide an overview of the literature pertaining to the impact of repeated IPC on cardiovascular function, related to both local and remote adaptation, as well as potential clinical implications. Abstract :